PROGRAM PENDIDIKAN KARAKTER BERBASIS RELIGIUS: Studi Kasus di SD Modern Paramadina Kediri - Anggara Dwinata; Hawwin Fitra Raharja; Eko Hardinanto; Emy Yunita Rahma Pratiwi; Aida Arini (An-Nahdliyyah: Jurnal Studi Keislaman, 2025)
The rise of radicalism and terrorism issues is partly due to the lack of support for character education in school educational institutions. The role of character education in the elementary school environment is very important, especially in building religious character. Religious character is one of the characters that guide students towards a generation with a high spiritual attitude. The achievement indicators are measured through a rubric for assessing attitudes and character periodically when students participate in daily, weekly, monthly, and yearly activities. Religious character can be realized through interesting activity programs. The purpose of this study is to describe religious character education at Paramadina Kediri Modern Elementary School. The research method used is a qualitative approach with a case study research design. The subjects in this study consisted of the Principal and Teachers. The results of the study describe several religious-based educational programs including congregational Dhuha Prayer, Morning Prayer Reading, Istighosah, Khotmil Al-Qur'an, Maqbaroh Pilgrimage, Yasin & Tahlil, Memorization of Short Surahs, Sholawat & Al-Banjari Art, Commemoration of Islamic Holidays, and Tadabur Alam. All of these programs are implemented in line with the school's curriculum and vision and mission. Through the existing activity program, it is hoped that it will become a habituation in order to improve the religious character of students at Paramadina Kediri Modern Elementary School.